Mulier cum sola cogitat male cogitat: the ruse of hetero-patriarchy (Balthazar, 2020)
Heteropatriarchy needs to permanently perpetuate the distinction between men and women as a legitimation of its own supremacy. This distinction works making the feminine a receptacle of all negative values and an element of contrast aimed to create male privilege. The myth of sexual difference is the psychic tool through which supremacy anchors on each individual creating categories like that of “abstract masculinity” and “concrete femininity”. In this frame the exclusion of women out of the field of knowledge, analyzed in its historical depth by Michèle Le Dœuff, appears as a tool of the perpetuation of heteropatriarchy, but when the exclusion does not occur properly and when some thinkers talk about rationality, flaws of this almost perfect systems come to the surface. It comes out that rationality is epicene, and it has a subversive charge towards the whole patriarchal structure. Nonetheless, myths are hard to die; as a psychic declination of a material oppression they place themselves as imaginary and shape individuals’ minds transforming them, very often, into oppressors of themselves. The “school of difference” seems doomed to this: becoming agents of the myth producing analysis that do not go further than the symptoms and false liberating instances. So, the need of a theory of oppression that keeps together the material level and the symbolic one, and of a theory of subjectivity that looks at the interdependence of individuals and collectivity, is reconfirmed. Critically analyzing the thought of Christine Delphy, this paper will try to lay the foundation to elaborate an alternative that suggests a coordinate action of liberation from material and symbolic oppression.
Keywords: oppression; rationality; antiessentialism; michèle le dœuff; feminisms